2018
DOI: 10.1371/journal.pone.0206213
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of reading subjective understanding based on eye gaze analysis

Abstract: The integration of ubiquitous technologies in the field of education has considerably enhanced our way of learning. Such technologies enable students to get a gradual feedback about their performance and to provide adapted learning materials. It is particularly important in the domain of foreign language learning which requires intense daily practice. One of the main inputs of adaptive learning systems is the user’s understanding of a reading material. The reader’s understanding can be divided into two parts: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…The experiments conducted only investigated the readers' observable reading behavior without examining their concrete understanding of the content. For this purpose, we follow the work of Sanches et al (2017Sanches et al ( , 2018) who in vestigated the readers' understanding of documents by using subjective comprehension questions and objective eye gaze data. Based on the work of Sanches et al (2017Sanches et al ( , 2018, we want to adapt the experimental design of our eye tracking study to create further replications of our experiment accord ing to the systematic approach for replication of experiments in software engineering by Gómez et al (2014).…”
Section: Future Workmentioning
confidence: 99%
See 2 more Smart Citations
“…The experiments conducted only investigated the readers' observable reading behavior without examining their concrete understanding of the content. For this purpose, we follow the work of Sanches et al (2017Sanches et al ( , 2018) who in vestigated the readers' understanding of documents by using subjective comprehension questions and objective eye gaze data. Based on the work of Sanches et al (2017Sanches et al ( , 2018, we want to adapt the experimental design of our eye tracking study to create further replications of our experiment accord ing to the systematic approach for replication of experiments in software engineering by Gómez et al (2014).…”
Section: Future Workmentioning
confidence: 99%
“…For this purpose, we follow the work of Sanches et al (2017Sanches et al ( , 2018) who in vestigated the readers' understanding of documents by using subjective comprehension questions and objective eye gaze data. Based on the work of Sanches et al (2017Sanches et al ( , 2018, we want to adapt the experimental design of our eye tracking study to create further replications of our experiment accord ing to the systematic approach for replication of experiments in software engineering by Gómez et al (2014). In this way, on the one hand, we increase the sample size to strengthen the conclusion validity of our findings.…”
Section: Future Workmentioning
confidence: 99%
See 1 more Smart Citation
“…driver's operations. For this issue, the gaze duration of the pedestrians at an AV has been focused in our study because the gaze duration is related to the levels of understanding [16,17,18,19,20]. We consider that the gaze duration could express pedestrians' requirements of understanding the driving intentions of an AV while also represent a degree of the pedestrian's understanding of the AV's driving intentions.…”
Section: State Of the Environmentmentioning
confidence: 99%
“…However, it is not easy to detect which part of the content they feel is difficult, even in e-book style that can collect clickstream data, because some pages include several topics on the same page. Text-based materials have similar problems, and previous research found that gaze features are effective for difficulty estimation [6], [7]. However, because of the characteristics of comics, information consists of illustrations and texts and is contained on one page, so it is complex compared to reading materials consisting of only text.…”
Section: Introductionmentioning
confidence: 99%